2013
DOI: 10.1063/1.4792520
|View full text |Cite
|
Sign up to set email alerts
|

The induction of nanographitic phase on Fe coated diamond films for the enhancement in electron field emission properties

Abstract: A thin layer of iron coating and subsequent post-annealing (Fe-coating/post-annealing) is seen to significantly enhance the electron field emission (EFE) properties of ultrananocrystalline diamond (UNCD) films. The best EFE properties, with a turn on field (E0) of 1.98 V/μm and current density (Je) of 705 μA/cm2 at 7.5 V/μm, are obtained for the films, which were Fe-coated/post-annealed at 900 °C in H2 atmosphere. The mechanism behind the enhanced EFE properties of Fe coated/post-annealed UNCD films are explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…7,8 Over past few years, many other nanomaterials, such as aligned carbon nanotubes, 10 ultra-nanocrystalline diamond lms, [11][12][13] arrays of gallium nitride nanorods, 14 titanium dioxide nanotubes, 15 cone-shaped zinc oxide nanostructures, 16 tin oxide nanotubes 17 and needle-shaped molybdenum trioxide 18 are showing much more e±ciency in¯eld emission with very low turn-on¯eld. Moreover ion implantation, 19 metallic coating 20 and H 2 surface treatment on diamond lms 21 are observed to signi¯cantly enhance the electron¯eld emission (EFE) properties. However, the lack of cost-e®ectiveness, ease in processing, highly packed emitting surfaces and compatible in fabrication limit the materials for applications in emitting device technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Over past few years, many other nanomaterials, such as aligned carbon nanotubes, 10 ultra-nanocrystalline diamond lms, [11][12][13] arrays of gallium nitride nanorods, 14 titanium dioxide nanotubes, 15 cone-shaped zinc oxide nanostructures, 16 tin oxide nanotubes 17 and needle-shaped molybdenum trioxide 18 are showing much more e±ciency in¯eld emission with very low turn-on¯eld. Moreover ion implantation, 19 metallic coating 20 and H 2 surface treatment on diamond lms 21 are observed to signi¯cantly enhance the electron¯eld emission (EFE) properties. However, the lack of cost-e®ectiveness, ease in processing, highly packed emitting surfaces and compatible in fabrication limit the materials for applications in emitting device technologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lack of cost-e®ectiveness, ease in processing, highly packed emitting surfaces and compatible in fabrication limit the materials for applications in emitting device technologies. In spite of high turn-on¯eld of bare SiNWs, availability of wide spectrum of synthesis procedure, [17][18][19][20][21][22] comparatively more dense emitting tips and above all compatibility in semiconducting vacuum microelectronic systems 8,28 make SiNWs°exible in electronics and optoelectronics device fabrication. The¯eld emission properties of SiNWs such as turn-on¯eld, emitting current density per unit area and¯eld enhancement factor can be signi¯cantly improved by functionalized coating of ultra-nanocrystalline diamond, 13,29 carbon nanotubes, 30 and various metallic thin¯lms 31 have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Various surface treatments have been conducted to enhance the field-emission properties of diamond films. Fe-coating and subsequent post-annealing is seen to enhance the EFE properties of diamond films. , Other studies show monolayer coatings of metals such as Co, Ni, Cu, Zr improved the emission properties of diamond films by shifting the position of the vacuum level. , It has been also reported that hydrogen treatment of diamond surfaces results in enhanced EFE properties . In the last few year,s the study of hydrogenated diamond surfaces has been a topic of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…It is to be noted that the conductivity of the a-C grain boundary phases of as-UNCD films is not sufficiently high, therefore limiting its conductivity and EFE properties [44,34]. However, it has been observed that the existence of grain boundary graphitic phases, surrounding the nanosized diamond grains are the prime factors for enhancing the conductivity and EFE properties [11,12,[35][36][37][38][39][40][41][42][43][44][45][46][47]. Similar conduction mechanism is proposed to explain the improved electron emission/conduction properties for doped-UNCD films.…”
Section: Discussionmentioning
confidence: 90%